2004
DOI: 10.1016/j.jtcvs.2004.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel and bleeding in patients undergoing elective coronary artery bypass grafting

Abstract: A strict transfusion algorithm can reduce the transfusion requirement for all blood components. Preheparin testing of platelet function with adenosine diphosphate aggregometry can identify patients at highest risk for perioperative bleeding and transfusions and might further reduce the perioperative transfusion requirement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
104
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(108 citation statements)
references
References 29 publications
1
104
0
3
Order By: Relevance
“…The surgery was successful, clopidogrel and aspirin were restarted eight hours later with loading doses, and the patient did not experience any thrombotic or bleeding events during the perioperative period [19]. Small studies have shown that adenosine diphosphate aggregometry, multiple electrode platelet aggregometry, and thromboelastography platelet mapping may be able to predict bleeding risks for patients receiving coronary artery bypass grafts (CABG) [20][21][22]. However, one of those studies showed that the point-of-care tests Platelet Function Analyzer 100 and Platelet Works were not predictive of which patients receiving CABG would bleed [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surgery was successful, clopidogrel and aspirin were restarted eight hours later with loading doses, and the patient did not experience any thrombotic or bleeding events during the perioperative period [19]. Small studies have shown that adenosine diphosphate aggregometry, multiple electrode platelet aggregometry, and thromboelastography platelet mapping may be able to predict bleeding risks for patients receiving coronary artery bypass grafts (CABG) [20][21][22]. However, one of those studies showed that the point-of-care tests Platelet Function Analyzer 100 and Platelet Works were not predictive of which patients receiving CABG would bleed [20].…”
Section: Discussionmentioning
confidence: 99%
“…Small studies have shown that adenosine diphosphate aggregometry, multiple electrode platelet aggregometry, and thromboelastography platelet mapping may be able to predict bleeding risks for patients receiving coronary artery bypass grafts (CABG) [20][21][22]. However, one of those studies showed that the point-of-care tests Platelet Function Analyzer 100 and Platelet Works were not predictive of which patients receiving CABG would bleed [20]. The VerifyNow P2Y 12 Test has not yet been studied to predict bleeding risks in CABG or other surgeries in patients taking clopidogrel [17].…”
Section: Discussionmentioning
confidence: 99%
“…We identified bleeding events in 12% of 201 subjects with aggregation rates of 20%, which was comparable to the bleeding event rate for an INR of 3.0-4.4 in Italian subjects taking warfarin 14) . Chen and colleagues 15) examined the relationship between platelet aggregation and bleeding during coronary bypass grafting and found that patients who had greater clopidogrel-induced platelet inhibition required a significantly higher number of platelet and red blood cell transfusions than patients with lower clopidogrel-induced platelet inhibition. This may support our major result, suggesting the possibility of using a platelet function assay as a tool for the risk stratification of bleeding events.…”
Section: Discussionmentioning
confidence: 99%
“…Current guidelines recommend that aspirin be continued until the time of surgery as RCTs have indicated that, although this increases blood loss marginally, there are no serious adverse events attributable to this blood loss and there are clear benefits in terms of fewer adverse cardiovascular events prior to surgery. 60 Observational analyses demonstrate more severe bleeding and adverse events attributable to platelet inhibition with DAPT relative to aspirin alone 61,62 and current guidelines (class I recommendation, evidence level B) recommend that P2Y 12 receptor antagonists be stopped 3-5 days prior to surgery. 24 This empirical approach is not without risk; many patients may be left at increased risk of adverse cardiovascular events prior to surgery and this is not detected by observational studies that commonly analyse events from surgery, a form of lead time bias.…”
Section: Antiplatelet Agentsmentioning
confidence: 99%